Determinants of dairy products purchase decisions among polish doctors: A gender-based analysis - Anna Nowak; Aneta Jarosz-Angowska; Artur Krukowski; Agnieszka Komor; Anna Goliszek; Sebastian Białoskurski; Bartosz G. Sołowiej; Katarzyna E. Przybyłowicz; Katarzyna Staniewska; Aneta Dąbrowska (PLoS ONE, 2026)
The study aimed to address a research gap by identifying the factors that influence the purchasing decisions of individual Polish doctors in the dairy products market, with gender as a demographic variable. The primary data collection method was a survey, conducted using the CAPI (Computer-Assisted Personal Interviewing) technique. The sample was selected using a purposive approach with elements of proportional territorial allocation. The survey involved 201 interviews with doctors from across Poland representing various fields of medical specialisation. The group of respondents surveyed is characterised by one of the highest levels of social trust. Conducting research among a professional group of doctors who are perceived as experts, whose knowledge is based on scientific evidence and many years of education, is an important contribution to the discussion on the factors that shape purchasing behaviour. The research confirmed the hypothesis that purchasing decisions in the dairy market are shaped by diverse factors. The study showed that the surveyed group of doctors most often makes purchasing decisions guided not only by health and quality values, but also by pragmatic ones, such as a product’s shelf life or availability in shops. The conducted research showed that differences between women and men representing the medical community in the assessment of factors influencing purchasing decisions in the dairy products market occur for 6 of the 26 variables assessed, thus one of the research hypotheses was only partially confirmed. Further research using principal component factor analysis made it possible to determine what hidden factors influence purchasing decisions among all respondents and groups distinguished by the demographic characteristic of gender, which allowed for the definition of customer segments.